Eastern attitudes to Rome during the Acacian schism - Frend, W. H. C. (Studies in church history, 1976)
The Acacian schism which lasted from 484 to 519 has been regarded as a bitter affair, characterised by intransigence on both sides and ending in an unqualified disaster for the Byzantine church. A closer look at the evidence suggests that the rigid attitudes of popes Gelasius (494-8) and Hormisdas (514-23) were far from being reproduced on the Byzantine side even at moments of provocation, and among the populace as a whole its existence was for most of the time a matter of indifference. The eventual ending of the schism through the initiative of the emperor Justin I was not regarded in the east as involving a derogation of the rights of the eastern patriarchates and of the church at Constantinople in particular.